INCREASE IN RAT BRAIN TYROSINE HYDROXYLASE ACTIVITY PRODUCED BY ELECTROCONVULSIVE SHOCK - Musacchio, Jose M. (1969)
A sustained increase in the turnover of norepinephrine coupled with an increased concentration of that amine has, in a previous study, been observed in the brains of rats exposed to electroconvulsive shock twice daily for one week. The phenomenon has been further examined by studying the effects of a similar regimen of electroconvulsive shock upon tyrosine hydroxylase in the brain, since that enzyme appears to be rate-limiting in norepinephrine synthesis. A small (15%) but significant increase in the whole brain enzyme activity was found in the electroshock-treated animals. A significant increase of tyrosine hydroxylase activity was found in the brainstem (24%) and cortex (20%) of such animals.